Analisis Perkembangan Ekspor Impor Sektor Nonmigas Di Provinsi Jawa Barat - Ronisa; Nona Siti Nuraisyah; Nabilla Salma Latifha; Nabila Putri Azahra; Elsa Anggraeni; Dilla Amalia Robiha; Hesti Puspita Alawiah; Ricky Firmansyah (Student Scientific Creativity Journal, 2023)
The development of world globalization at this time has resulted in all countries having to be able to adapt to the changes that have occurred. One of the impacts of globalization is the growing development of international markets which has led to more open export and import activities between countries. Export activities are activities of selling goods abroad, while import activities are the opposite, namely activities of buying goods from abroad. The development of import and export can improve the country's economy if it is managed effectively. Commodities that are often exported and imported are the non-oil and gas sector. Non-oil and gas itself stands for non-oil and gas. Export and import activities in the non-oil and gas sector in each province tend to be different and fluctuate, one of which is in West Java Province. This analysis aims to determine the development of the non-oil and gas export-import sector in West Java Province. The research method used in this analysis is to use qualitative methods by collecting data using literature study techniques collected through data from West Java BPS (Central Statistics Agency) regarding non-oil and gas exports and imports according to Goods Class (Millions USD) in 2013-2017. The results of this analysis show that (1) the export-import performance of the group of non-oil and gas goods in West Java Province from 2013 to 2017 shows an instability that can be seen in the value of imports, then an increase in the value of exports; (2) The trade balance shows a positive value, meaning that foreign trade in the non-oil and gas sector is dominated by exports.